Practices in Integrating Workplace Learning into Upper Secondary Education - Birgit Peterson; Krista Loogma; Maret Aasa (Social Sciences)
In recent years, Estonian employers, upper secondary schools, and other stakeholders have devised various new collaborative measures to effectively integrate workplace learning (WPL) and school education. These efforts are aimed at enhancing the key competences of students. However, the educational purpose and effectiveness of the various initiatives are unknown. The main aim of this research is to explore what kinds of practises are applied in Estonian upper secondary schools to integrate formal education and WPL, and the experiences and requirements of schools and employers in this area. The empirical study is based on individual and focus group interviews conducted with upper secondary school teachers, head teachers, and employers. A phenomenological approach and inductive thematic analysis were used to examine current practises. The results of the study show that workplace learning is integrated into school learning mainly for the development of key competences and career competencies. An important part of the learning process is reflecting on experiences implemented via institutional cooperation. In core or foundation subjects, especially STEM subjects, the topics of work life or recognition of work experience are rarely encountered in school.